JOURNAL OF GOVERNMENT & POLITICS : Gender Discourse and Women Movements in Nahdlatul Ulama (NU) - Dian Eka Rahmawati (FISIPOL UMY, 2015)
The involvement of NU gender activist with the feminism ideas, the strengthening of democracy issues in Islam.